Necessary generalization of Кlein-Gordon and Dirac equations and existence of particle generations - Kulish, Yu.V.; Rybachuk, E.V. (Вопросы атомной науки и техники, 2012)
It is shown that values of the Green functions for the Klein-Gordon and Dirac equations depend on calculation method. The integrals for the Green functions of new equations can converge if the minimal numbers of the particles equal three for spinless particles and five for 1/2-spin particles. It leads to the existence of massive generations for the photon and the gluons. It is shown that the interaction potentials have oscillatory form at short distances.